Estudio comparativo de dos métodos estadísticos de estimación robusta para optimizar un portafolio con activos de renta variable del mercado bursátil colombiano (2024)
The research focuses on improving the investment decision-making process by building more stable and efficient optimal portfolios. Robust statistical estimation methods, such as the Covariance Matrix with Minimum Determinant (MCD) method and the Minimum Volume Ellipsoid (MEV) method, are compared with the classic Minimum Variance model. A quantitative research approach was used to objectively evaluate the effectiveness of these methods in constructing investment portfolios with companies listed on the Colombian Stock Exchange (BVC). Stock prices were obtained from the “Yahoo Finance!" platform and the models were implemented using the scientific program R.